Representasi Sejarah dan Dampak Perang Dunia II dalam Komik Kono Sekai No Katasumi Ni Karya Fumiyo Kouno - Reza Taufan Adhitya; Renny Anggraeny; Ida Ayu Laksmita Sari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to find out and understand the representation of the history of World War II and the impact of World War II on the Japanese, especially the people who live in Kure in the comic Kono Sekai no Katasumi ni by Fumiyo Kouno. The method used in this study is the descriptive analysis method. The theory used in this study is the theory of New Historicism by Stephen Greenbalt. The results show, there are five historical facts, the establishment of tonarigumi, the creation of the tatemono sokai policy, the air attack on Kure, the attack on the Hiro Naval Base, and the dropping of Atomic Bomb on Hiroshima, which also affected Kure area which is 20 kilometres to southeast Hiroshima. In addition, as a result of the occurrence of World War II, the mindset of the Japanese people regarding war changed from those previously zealous in warfare to preferring to maintain peace. On the other hand, the impact of World War II is still being felt today by the Japanese people, especially for victims who survived and were still alive until the time this comic was published.